Utilization of post-exposure prophylaxis potentially contributed to the changes of risk behaviors among men who have sex with men in China - Rong Su; Yi Liu; Peilong Li; Lin Ge; Meizhen Liao; Yong Fu; Xin Song; Houlin Tang; Dongmin Li (Frontiers Media S.A., 2024)
BackgroundThe HIV infection status among men who have sex with men (MSM) in China is a cause for concern. Post-exposure prophylaxis (PEP) serves as a highly effective biomedical preventive measure against HIV infection. Substantial evidence has established an association between PEP utilization and risk behaviors among MSM, but whether the utilization of PEP has an impact on risk behaviors remains unknown. This study sought to elucidate the impact of PEP usage on risk behaviors among MSM and provide recommendations for developing targeted HIV prevention programs.MethodsA cohort study was conducted in Qingdao, China, from April 2021 to January 2022. Participants were enlisted by volunteers from community-based organizations through a snowball sampling method. Face-to-face interviews were conducted to collect sociodemographic and behavioral information of participants. The study encompassed a retrospective investigation, baseline survey, and follow-up survey, representing periods before, during, and after PEP usage, respectively. Generalized estimating equations, fitting a Poisson regression model, were applied to scrutinize changes in risk behaviors of MSM during and after PEP usage, in comparison to before PEP usage.ResultsA total of 341 MSM were recruited in the cohort study, with 179 individuals completing the follow-up survey. In comparison to before PEP usage, there was a significant increase in the proportion of Rush Popper usage (17.6% vs. 23.8% vs. 29.6%) and commercial sexual partners (10.9% vs. 17.6% vs. 21.8%) among MSM during and after PEP usage. Before PEP usage, 88.7% of MSM reported having ≥3 temporary sexual partners in the last 6 months. This proportion exhibited no significant change during PEP usage (91.8%), but it significantly increased to 97.8% after PEP usage (P < 0.05). Notably, there was a significant decrease in group sex during and after PEP usage compared to before PEP usage (30.8% vs. 21.4% vs. 21.2%).ConclusionThe utilization of PEP may impact risk behaviors among MSM, potentially leading to increased Rush Popper usage, temporary sexual partners, and commercial sexual partners after PEP usage, accompanied by a decrease in group sex. Further research is imperative to elucidate the impact of PEP utilization on MSM and develop targeted HIV prevention programs.